LIBERALISASI PENDIDIKAN DALAM KERANGKA GATS : KAJIAN HUKUM TERHADAP PENDIRIAN PERGURUAN TINGGI ASING DI INDONESIA - Anggiat Simamora; Bismar Nasution; Suhaidi Suhaidi; Mahmul Siregar (USU LAW JOURNAL, 2014)
ABSTRACTHigher education liberalization facilitated by the WTO/ GATS has distorted the nature of education as a public service in Indonesia. This study aims at finding out 1). How HE in Indonesia is regulated, 2). what the existence of foreign higher education in the Indonesian regulation is, and 3) what the impact of GATS on regulating higher education in Indonesia is. It was found out that 1). both public higher education (PTN) and Private higher education (PTS) conduct governmental authority. Otherwise, the regulations threat them discriminately, 2). Foreign HE is recognized in Indonesian regulation as a part of SPN. Consequently, foreign HE instututions legally cannot be established in Indonesia, 3). GATS impacts on regulating HE in Indonesia since all agreements achieved in WTO/GATS abide Indonesia. From these findings, it is suggested that 1 ) . Government threat both PTN and PTS equally since they are held in the same system, 2). Regulation obliging foreign higher education to be held as parts of SPN be maintained to improve the quality of Indonesia higher education, 3). Indonesia makes a new legislation on higher education industry.Keywords : Liberalization , Higher Education , SPN , GATS